Publication manual of the American Psychological Association (American Psychological Association, 2010)
From the Publisher: With millions of copies sold, the Publication Manual of the American Psychological Association is the style manual of choice for writers, editors, students, educators, and professionals in psychology, sociology, business, economics, nursing, social work, and justice administration, and other disciplines in which effective communication with words and data is fundamental. In addition to providing clear guidance on grammar, the mechanics of writing, and APA style, the Publication Manual offers an authoritative and easy-to-use reference and citation system and comprehensive coverage of the treatment of numbers, metrication, statistical and mathematical data, tables, and figures for use in writing, reports, or presentations. The new edition has been revised and updated to include: The latest guidelines and examples for referencing electronic and online sources; New and revised guidelines for submitting papers electronically; Improved guidelines for avoiding plagiarism; Simplified formatting guidelines for writers using up-to-date word-processing software; All new guidelines for presenting case studies; Improved guidelines for the construction of tables; Updates on copyright and permissions issues for writers. New reference examples for audiovisual media and patents; An expanded and improved index for quick and easy access; Writers, scholars, and professionals will also find: New guidelines on how to choose text, tables, or figures to present data; Guidelines for writing cover letters for submitting articles for publication, plus a sample letter; Expanded guidelines on the retention of raw data; New advice on establishing written agreements for the use of shared data; New information on the responsibilities of co-authors.